Originate, motivate, innovate 7 steps for building a billion dollar network - Bell, Shelly Omilâdé (Ascent Audio, 2023)
Supercharge your business or career by staying true to your authentic self In Originate, Motivate, Innovate, accomplished entrepreneur Shelly Omilâde Bell and author Sheena C. Howard deliver an honest and engaging discussion of how to think differently about getting your business funded as a female entrepreneur of color. In the book, you'll find the mindsets, tools, tactics, and strategies you need to succeed in a venture capital environment that is largely designed by-and for-white males. You'll learn how to apply your own unique story and background and prioritize valuable relationships to create your own pathway to a fully funded business. You'll also discover: - An acknowledgment and highlighting of those obstacles that remain in place and stand in the way of women of color in business - How to break through those obstacles while doing things your own way - Strategies for achieving your next goal, whether that's building a business, creating social impact, or looking for a raise An essential resource for entrepreneurs, founders, and other business leaders of color, Originate, Motivate, Innovate is the no-nonsense, hands-on book that professional women of color have been waiting for.